Improved umac algorithm with crypto-code mceliece's scheme - Yevseiev, S. P.; Havrylova, Alla (Premier Publishing s.r.o., Austria, 2020)
The article discusses the mathematical model of the mini-version of the UMAC hashing algorithm, using various cryptoalgorithms as a pseudo-random substrate when generating key data, presents the results of studies of the considered mini-versions. A new approach is proposed to ensure the cryptographic stability of this hashing algorithm based on Mac-Elis crypto-code constructions on modified elliptic codes. This approach will provide the required level of cryptographic security in post-quantum cryptography.
Keywords: Mac-Elis crypto-code; UMAC hashing algorithm; El-Gamal cryptosystems